GATES/GEB as the Best Thermodynamic Approach to Electrolytic Redox Systems - a Review - Anna, M. Michałowska-Kaczmarczyk; Tadeusz, Michałowski (Journal of New Developments in Chemistry, 2020)
The Generalized Approach To Electrolytic Systems (GATES) provides the best possible thermodynamic formulation of redox and non-redox, equilibrium and metastable, mono-, two- and three-phase systems, with all attainable/pre-selected physicochemical knowledge involved, without any simplifying assumptions made for calculation purposes, where different species may occur in batch or dynamic systems, of any degree of complexity. The Generalized Electron Balance (GEB) is the key concept completing the set of algebraic balances referred to redox systems, described according to GATES/GEB ⊂ GATES principles. The GEB, considered as the law of Nature, is fully compatible with charge and concentration balances, and relations for the corresponding equilibrium constants. Within GATES, the electrolytic systems are resolvable with use of MATLAB, or other iterative computer programs, if all necessary physicochemical knowledge is attainable.
Keywords: Electrolytic redox systems; GATES; GEB; GATES/GEB; Computer simulations.